EVALUATION OF POLICIES TO IMPROVE CLEAN WATER SERVICES BY THE TIRTA BENTENG REGIONAL PUBLIC UTILITY COMPANY TANGERANG CITY - Alfhina Aulia Putri; Raden Imam Al Hafis (Indonesian Journal of Social Sciences, Policy and Politics, 2026)
Clean water access is a fundamental need that significantly affects public health and quality of life, making Perumda Tirta Benteng Tangerang City responsible for providing reliable water services. This study evaluates the clean water service improvement policy by examining effectiveness, supporting and inhibiting factors, and public satisfaction. A descriptive qualitative approach was employed using interviews, observation, and documentation. The findings indicate that policy effectiveness remains suboptimal due to aging infrastructure, limited technical human resources, and weak inter-agency coordination. Digital complaint services support improvements, yet technical distribution issues remain dominant barriers. Public satisfaction varies across service areas. This study recommends accelerating pipe network rejuvenation, strengthening technical capacity, improving transparency, and enhancing inter-agency collaboration.